Prospecting of Mannan Degrading Bacteria on Treating Palm Kernel Meal - Ludovika Jessica Virginia; Yepy Hardi Rustam; Griselda Herman Natadiputri; Antonius Suwanto (International Journal of Oil Palm, 2018)
Palm kernel meal (PKM) is one of the most abundant by-products from oil palm industries. Although PKM can be used as ruminant feed but unfortunately it can not be applied directly as chicken feed due to its complex structure and lack of mannan degrading enzyme in chicken. Manan is a complex molecule composed of linear mannan, glucomannan, galactomannan, and galactoglucomannan and most nutrition contained in PKM was trapped in mannan structure. To increase the economic value of PKM, utilization of mannan degrading enzyme in pretreatment process of PKM before applying as chicken feed is required. We report here that isolation of potential mannanase as well as its prospective toward application in PKM was successfully conducted in this study. Mannanase producing bacteria (CK7) harboring wild type ?-mannanase activity at 48.03 U mL-1 was obtained and identifed as Bacillus subtilis isolate qd386 (accession number EF473134) with 96.7% pairwise identity through 16s amplifcation. Over expression in Pichia pastoris system by pPICZ?A as vector and KM71 as host (P-CK7) improved its activity into 4207.56 U mL-1 and 5000 U mL-1 within fed batch fermentation at 7.5 L and 500 L, respectively. Recombinant manCK7 generated from P-CK7 was reported as the major expressed extracellular protein through SDS-PAGE in this study, thus make it more benefcial and attractive for further application study due to reduction of cell breaking process. Preliminary study on manCK7 application to PKM showed a promising result with a signifcant sugar released observed between PKM which treated with bu?er, commercial enzyme, and manCK7 for 89 µmole, 460.6 µmole, and 518.2 µmole, respectively.